Urgensi Fungsionalisasi Teori Hukum Dalam Proses Pembentukan Hukum Pidana di Indonesia (Faculty of Law, Maranatha Christian University, 2018)
Criminal law is a means for regulating public orders. Criminal law is prevailed by applying written law, because criminal law is bounded by legality principle. Formulation of legal substance in criminal law system is influenced by how the lawmaker formulate words to be communicated to the society. It’s not only about a technical stage, but also related to theoretical aspect of law, about how rules enforceability, and how logical principles and legal reasoning applied in lawmaking process. Formulation of rules in RKUHP still facing several problems. It’s interesting to know how legal theories should be applied in criminal law-making process. This research was done with normative juridical method.Primary legal materials such as regulations and secondary legal materials such as literature and legal theories were analyzed with deductive reasoning steps. The conclusions, legal theories have corelation with lawmaking process, as doctrine of method. By understanding and performing it, hopefuly lawmakers can formulate ideal legal norms. Legal theories also required for preserving rationality of how criminal actions are formulated in the Code and avoiding fallacies in formulation of criminal conducts.